Melanocortin‐3 Receptors Expressed on Agouti‐Related Peptide Neurons Inhibit Feeding Behavior in Female Mice. Issue 12 (14th November 2018) - Girardet, Clemence; Marks, Daniel L.; Butler, Andrew A.
Abstract : Objective: Activation of hypothalamic agouti‐related peptide expressing ( AgRP ) +ve neurons during energy deficit is a negative valence signal, rapidly activating food‐seeking behaviors. This study examined the roles of melanocortin‐3 receptors (MC3Rs) coexpressed in a subpopulation of AgRP +ve neurons. Methods: AgRP‐MC3R mice expressing MC3Rs selectively in AgRP +ve neurons were generated by crossing AgRP‐IRES‐Cre mice with LoxTB Mc3r mice containing a "loxP‐STOP‐loxP" sequence in the 5′ untranslated region. Body weight, body composition, and feeding behavior were assessed during ad libitum and time‐restricted feeding conditions. Results: In females, food intake of AgRP‐IRES‐Cre +ve ( n = 7) or AgRP‐IRES‐Cre ‐ve ( n = 9) mice was not significantly different; these mice were therefore pooled to form the "control" group. Female AgRP‐MC3R mice exhibited lower food intake (25.4 ± 2.4 kJ/12 h; n = 6) compared with controls (35.3 ± 1.8 kJ/12 h; n = 16) and LoxTB Mc3r mice (32.1 ± 2.1 kJ/12 h; n = 9) in the active phase during the dark period. Food intake during the rest phase (lights on) when mice consume less food (9‐10 kJ) was normal between genotypes. Body weight and composition of AgRP‐MC3R and LoxTB Mc3r mice were similar, suggesting compensatory mechanisms for reduced calorie intake. Remarkably, AgRP‐MC3R mice continued to consume less food during refeeding after fasting and time‐restricted feeding. Conclusions: MC3Rs expressed on AgRP +ve neurons appear to exert a strong inhibitory signal on hypothalamic networks governing feeding behavior.